Phytochemical Analysis and Trypanocidal Activity of Marrubium incanum Desr. - Claudio Frezza; Alessandro Venditti; Armandodoriano Bianco; Mauro Serafini; Massimo Pitorri; Fabio Sciubba; Maria Enrica Di Cocco; Eleonora Spinozzi; Loredana Cappellacci; Anders Hofer; Filippo Maggi; Riccardo Petrelli (Molecules, 2020)
The rationale inspiring the discovery of lead compounds for the treatment of human parasitic protozoan diseases from natural sources is the well-established use of medicinal plants in various systems of traditional medicine. On this basis, we decided to select an overlooked medicinal plant growing in central Italy, Marrubium incanum Desr. (Lamiaceae), which has been used as a traditional remedy against protozoan diseases, and to investigate its potential against Human African trypanosomiasis (HAT). For this purpose, we assayed three extracts of different polarities obtained from the aerial parts of M. incanum—namely, water (MarrInc-H2O), ethanol (MarrInc-EtOH) and dichloromethane (MarrInc-CH2Cl2)—against Trypanosoma brucei (TC221), with the aim to discover lead compounds for the development of antitrypanosomal drugs. Their selectivity index (SI) was determined on mammalian cells (BALB/3T3 mouse fibroblasts) as a counter-screen for toxicity. The preliminary screening selected the MarrInc-CH2Cl2 extract as the most promising candidate against HAT, showing an IC50 value of 28 μg/mL. On this basis, column chromatography coupled with the NMR spectroscopy of a MarrInc-CH2Cl2 extract led to the isolation and identification of five compounds i.e. 1-α-linolenoyl-2-palmitoyl-3-stearoyl-sn- glycerol (1), 1-linoleoyl-2-palmitoyl-3-stearoyl-sn-glycerol (2), stigmasterol (3), palmitic acid (4), and salvigenin (5). Notably, compounds 3 and 5 were tested on T. brucei, with the latter being five-fold more active than the MarrInc-CH2Cl2 extract (IC50 = 5.41 ± 0.85 and 28 ± 1.4 μg/mL, respectively). Furthermore, the SI for salvigenin was >18.5, showing a preferential effect on target cells compared with the dichloromethane extract (>3.6). Conversely, stigmasterol was found to be inactive. To complete the work, also the more polar MarrInc-EtOH extract was analyzed, giving evidence for the presence of 2″-O-allopyranosyl-cosmosiin (6), verbascoside (7), and samioside (8). Our findings shed light on the phytochemistry of this overlooked species and its antiprotozoal potential, providing evidence for the promising role of flavonoids such as salvigenin for the treatment of protozoal diseases.